(untitled) - Sidnie Feit (New York, 1993)
The book offers a comprehensive coverage of the core protocols - IP, ICMP, TCP, UDP, FTP, SMTP, and TELNET - and the additional services available with most TCP/IP products - NFS, NIS, BIND, ARP, RIP, KERBEROS, SNMP, and programmig interfaces. Emphasizing practical applications illustrated with examples, interactive dialogues, and traces, the book contains complete detais for planning, installing, using, operating, and maintaining a TCP/IP network and its associated services. In addition, the differences between TCP/IP and the OSI protocol suite are compared and migration issues exlored
Keywords: tcp/ip ( computer network protocal )